Missio Maritatus in the Missio Dei:Genesis 1:28 for Marriage Missiology - Jonas Sello Thinane (E-Journal of Humanities, Arts and Social Sciences, 2024)
Marriage is a sacred institution that represents God’s sent interpersonal relationships to proliferate humanity, rather than just the act of remaining as husband and wife. The phrase “be fruitful, multiply, and subdue the earth” is perhaps a better way to describe this missio maritatus, or marriage mission, as God instructs humanity in Genesis 1:28. God, the eternal missionary here, calls on humanity to be fruitful, multiply, and steward the earth. Although missiology has frequently examined how marriage intersects with redemptive goals within the complex framework of missio Dei, no study has formally introduced the theoretical framework of missio maritatus. This paper therefore presented the theoretical underpinnings of missio maritatus, which embraces the complexity of missio Dei and interprets Genesis 1:28 as expressing marriage missiology. It firmly based this mission’s theoretical framework on the central Christian doctrines of predestination and divine foresight. It states unequivocally that the limited traditional understanding of marriage still has issues, but it leaves it to future studies to define missio maritatus in light of contemporary marriage trends. To put it another way, despite its shortcomings, missio maritatus is a useful theoretical framework in missiology, and the scope of this paper justifies further investigation into this area. This paper makes two important contributions to the respective areas of theology: The first and most general part concerns practical theology, as it examines the intersection of marriage with broader Christian social theological teachings. Second, and perhaps more importantly, the novel development of the missio maritatus in missiology adds a new missio-theological framework which incorporates the institution of marriage with the context of the missio Dei.